The Contribution of Digital Marketing to Business Performance: The Case of Companies in the Northern Region of Morocco - El Hachimi, Ikram; Ait Lhassan, Imad; Belamhitou, Mahmoud (European Scientific Journal, ESJ, 2021)
Digital marketing is revolutionizing the organizational structures and offers companies, especially Moroccan companies, a multitude of opportunities to evolve the classic business model to innovate in products and services while building a direct and personalized relationship with customers. Indeed, digital marketing highlights important features for companies seeking efficiency and performance, and it considers an attractive alternative to traditional approaches as a response to the challenges of globalization. The ultimate objective of our research is to confirm the direct relationship between digital marketing and the business performance of companies in the northern region of Morocco. The result of the study was noted by many authors. On this matter, we have conducted a quantitative survey carried out among 120 companies in the northern region of Morocco using the PLS path modeling, a method particularly suited for academic development and predictive applications. According to our empirical study, we found that digital marketing has a positive impact on the performance of companies in the northern region of Morocco.